South Sudan's Infrastructure : A Continental Perspective - Ranganathan, Rupa (World Bank, Washington, DC, 2017)
This study is a product of the Africa Infrastructure Country Diagnostic (AICD), a project designed to expand the world's knowledge of physical infrastructure in Africa. AICD provides a baseline against which future improvements in infrastructure services can be measured, making it possible to monitor the results achieved from donor support. It also offers a solid empirical foundation for prioritizing investments and designing policy reforms in Africa's infrastructure sectors. The AICD is based on an unprecedented effort to collect detailed economic and technical data on African infrastructure. The project has produced a series of original reports on public expenditure, spending needs, and sector performance in each of the main infrastructure sectors, including energy, information and communication technologies, irrigation, transport, and water and sanitation. This report presents the key AICD findings for South Sudan, allowing the country's infrastructure situation to be benchmarked against that of its African peers. South Sudan is a newly independent country, affected by conflict, endowed with oil, but poor in terms of infrastructure and economic development. Because of these factors, both low-income, fragile states and resource-rich benchmarks will be used to evaluate its performance. Detailed comparisons will also be made with immediate regional neighbors in the East African Community (EAC).